Analysis of Socio-demographic Factors of Dental and Oral Hygiene among Pregnant Women - Enni Kustiyah; Sitti Nur Djannah; Lina Handayani; Intan Wahyuni Tukiyo (Jurnal EduHealth, 2023)
Dental and oral diseases still have a significant impact, especially on pregnant women. Pregnant women are vulnerable to dental and oral diseases such as periodontitis, gingivitis and dental caries. This study aims to determine the relationship between the characteristics of pregnant women and the oral hygiene of pregnant women at the Banguntapan II Public Health Center (PHC), Bantul District, Yogyakarta Province. This research uses an analytical observational method with a cross sectional design. The research population was pregnant women who were registered at the PHC in the last 3 months. The sample was taken using the accidental sampling technique totaling 90 people. Data collection was carried out using a social demographic questionnaire and the OHI-S (Oral Hygiene Index-Simple) questionnaire. The data obtained was analyzed using chi-square. The results of the study showed that there was no significant relationship between maternal age (p-value 0.222), education level (p-value 0.716) and employment status (p-value 0.763) on dental and oral hygiene of pregnant women. Therefore, socio-demographic characteristics have no relationship to oral hygiene during pregnancy. For this reason, it is necessary to test other variables to see the factors that cause dental and oral disease in pregnant women.